Expression of 19 microRNAs in glioblastoma and comparison with other brain neoplasia of grades I–III. Issue 2 (24th December 2013) - Visani, Michela; de Biase, Dario; Marucci, Gianluca; Cerasoli, Serenella; Nigrisoli, Evandro; Bacchi Reggiani, Maria Letizia; Albani, Fiorenzo; Baruzzi, Agostino; Pession, Annalisa; ,
Abstract : Several biomarkers have been proposed as useful parameters to better specify the prognosis or to delineate new target therapy strategies for glioblastoma patients. MicroRNAs could represent putative target molecules, considering their role in tumorigenesis, cancer progression and their specific tissue expression. Although several studies have tried to identify microRNA signature for glioblastoma, a microRNA profile is still far from being well‐defined. In this work the expression of 19 microRNAs (miR‐7, miR‐9, miR‐9∗, miR‐10a, miR‐10b, miR‐17, miR‐20a, miR‐21, miR‐26a, miR‐27a, miR‐31, miR‐34a, miR‐101, miR‐137, miR‐182, miR‐221, miR‐222, miR‐330, miR‐519d) was evaluated in sixty formalin‐fixed and paraffin‐embedded glioblastoma samples using a locked nucleic acid real‐time PCR. Moreover, a comparison of miRNA expressions was performed between primary brain neoplasias of different grades (grades IV–I). The analysis of 14 validated miRNA expression in the 60 glioblastomas, using three different non‐neoplastic references as controls, revealed a putative miRNA signature: mir‐10b and miR‐21 were up‐regulated, while miR‐7, miR‐31, miR‐101, miR‐137, miR‐222 and miR‐330 were down‐regulated in glioblastomas. Comparing miRNA expression between glioblastoma group and gliomas of grades I–III, 3 miRNAs (miR‐10b, mir‐34a and miR‐101) showed different regulation statuses between high‐grade and low‐grade tumors. miR‐10b was up‐regulated in high grade and significantly down‐regulated in low‐grade gliomas, suggesting that could be a candidate for a GBM target therapy. This study provides further data for the identification of a miRNA profile for glioblastoma and suggests that different‐grade neoplasia could be characterized by different expression of specific miRNAs. Highlights: MicroRNA profiles in glioblastoma depend on used non‐neoplastic reference. Glioblastomas are characterized by a specific miRNA expression pattern. Low‐grade brain neoplasias show different miRNA expression values than glioblastomas.